Equal swept-area experimental comparison of savonius and H-type darrieus vertical axis wind turbines for floating net cages microloads - Herlina, Herlina; Nur, Tajuddin; Puspitasari, Dewi; Fitria, Syarifa (Edelweiss Applied Science and Technology, 2026)
Floating net cages (FNCs) in coastal aquaculture require a reliable, low-power electricity supply for daily operations. However, many coastal sites still have limited grid access and depend on fuel-based energy. This study compared the performance of a Savonius rotor and an H-type Darrieus rotor as renewable electricity options for FNC applications, using the same swept area of 0.45 m² and a shared direct-current generator interface under controlled laboratory airflow. A total of 560 operating points were recorded at wind speeds of 1.5–8.0 m/s under discrete resistive loads. Electrical power generation was derived from the measured voltage and current, while the wind-to-electric efficiency was determined as the proportion of generated electrical power to the available wind power. The findings indicated that the H-type Darrieus turbine exhibited superior performance compared to the Savonius turbine across the entire testing range. Its mean electrical power reached 7.59 W, compared with 4.47 W for the Savonius, while mean efficiency reached 17.01% and 10.09%, respectively. At 8.0 m/s, the H-type Darrieus produced 22.01 W, whereas the Savonius produced 12.47 W. These results indicate that the H-type Darrieus rotor is more suitable for the early-stage design of hybrid wind-solar-battery systems for FNC applications.